Tracing the tidal streams of the Sagittarius dSph, and halo Milky Way features, with carbon-rich long-period variables - Huxor, Avon P.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We assemble 121 spectroscopically confirmed halo carbon stars, drawn from the literature, exhibiting measurable variability in the Catalina Surveys.